Ghost in the Shell: Evidence for Past Active Galactic Nucleus Activities in NGC 5195 from a Newly Discovered Large-scale Ionized Structure - Xu, Xiaoyu; Wang, Junfeng (The Astrophysical journal, 2023)
The early-type galaxy NGC 5195 (alternatively known as M51b) possesses extended gas features detected in the multiwavelength, postulated to be associated with previous activities of the central supermassive black hole. Using integral field spectroscopic observations from the Canada–France–Hawaii Telescope/SITELLE, we report on the discovery of a new large-scale ionized gas structure traced by [O iii ], [N ii ], and H α line emission, extending to ∼10 kpc from the nucleus of NGC 5195. Its bipolar morphology, emission-line ratio diagnostics, and comparison with the X-ray image from Chandra and low-frequency radio data from LOFAR all indicate that it is likely an outflow inflated by a past episode of elevated active galactic nucleus (AGN) activity. Assuming the ionized gas is outflowing from the central region of NGC 5195, the estimated mass and energy outflow rates are M ̇ out = 3.5 –27.9 M ☉ yr −1 and E ̇ out = 0.98 –7.9 × 10 40 erg s −1 , respectively, which cannot be provided by current star formation and the low-luminosity nucleus. Alternatively, considering the history of gravitational interaction between the M51 pair and the presence of the H i tidal tail, the northern large-scale ionized gas could very likely be associated with tidally stripped material illuminated by a luminous AGN in the past.